2015
DOI: 10.1177/0022034514565647
|View full text |Cite
|
Sign up to set email alerts
|

Osterix Regulates Tooth Root Formation in a Site-specific Manner

Abstract: Bone and dentin share similar biochemical compositions and physiological properties. Dentin, a major tooth component, is formed by odontoblasts; in contrast, bone is produced by osteoblasts. Osterix (Osx), a zinc finger-containing transcription factor, has been identified as an essential regulator of osteoblast differentiation and bone formation. However, it has been difficult to establish whether Osx functions in odontoblast differentiation and dentin formation. To understand the role of Osx in dentin formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 32 publications
4
53
0
Order By: Relevance
“…While these findings support Alpl +/A116T mice as a model of odontohypophosphatasia, limitations included lack of defects in dentin and enamel and a mildly affected periodontium. In dentoalveolar tissues, the Col1a1-Cre line targets gene ablation to type I collagen-producing cells, including odontoblasts, osteoblasts, cementoblasts, and fibroblasts (Dacquin et al 2002;Kim et al 2012;Kim et al 2015). Col1a1-cKO mice recapitulated an array of classic human and mouse HPP dental defects, including short molar roots, thin dentin, widened pulp chambers, lack of acellular cementum, loss of attachment, and hypomineralized alveolar bone.…”
Section: Dental Defects In Mouse Models Of Late-onset Hppmentioning
confidence: 99%
“…While these findings support Alpl +/A116T mice as a model of odontohypophosphatasia, limitations included lack of defects in dentin and enamel and a mildly affected periodontium. In dentoalveolar tissues, the Col1a1-Cre line targets gene ablation to type I collagen-producing cells, including odontoblasts, osteoblasts, cementoblasts, and fibroblasts (Dacquin et al 2002;Kim et al 2012;Kim et al 2015). Col1a1-cKO mice recapitulated an array of classic human and mouse HPP dental defects, including short molar roots, thin dentin, widened pulp chambers, lack of acellular cementum, loss of attachment, and hypomineralized alveolar bone.…”
Section: Dental Defects In Mouse Models Of Late-onset Hppmentioning
confidence: 99%
“…Kim et al . () also investigated the effects of odontoblast‐specific inactivation of Osx . They confirmed that mutant mice displayed normal crowns but short molar roots and thin inter‐radicular dentine; the root elongation was also disturbed by impaired odontoblastic maturation.…”
Section: Site‐specific Function Of Osx In Root Formationmentioning
confidence: 99%
“…, Kim et al . ). First recognized in bone development, these genes participate in both the processes of osteogenesis and odontogenesis that share many common characteristics in the regulation mechanisms (Nakashima et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…We appreciate the letter to the editor from Dr. Feng in response to our article titled "Osterix Regulates Tooth Root Formation in a Site-specific Manner" (Kim et al 2015).…”
Section: Letters To the Editormentioning
confidence: 99%